Constructing political feasibility: argumentation and persuasion in the process of design and adoption of the National Policy on Modernization of Public Management between 2011 and 2013 - Benites Nieves, Rodolfo David (2014)
This paper documents the process of design and adoption of the «National Policy on Modernization of Public Management» between 2011 and 2013. In order to achieve this objective, it will identify the political, institutional and economic constrains and it will analyse the importance of various actor which policymaker had to engage for political legitimacy and formal approval.  This analysis fins that the implementation of a communication strategy produced the political consensus necessary for political approval.